Novel and efficient one-pot synthesis of spiro[indoline-3, 4'pyrano [2, 3-c]pyrazole]derivatives catalysed by L-proline in aqueous medium. (1st June 2013) - Yu, Jiangxia; Zhou, Yongbing; Shen, Tianhua; Mao, Wengang; Chen, Kang; Song, Qingbao
An efficient mild one-pot synthesis of spiro[indoline-3, 4'-pyrano[2, 3-c]pyrazole derivatives by a four-component reaction of hydrazine, a β-keto ester, isatin, and malononitrile catalysed by L-proline in water is reported.